Perancangan Interior Restoran Dengan Pendekatan Ekologis Di Surabaya - Herlin Sri Utami, Felix .T. Adi Santosa (Intra, 2013)
Surabaya City has a good prospect in the culinary sectorÂ such as, opening a restaurant business, looking at the people who make the food as a culinary tour. This consuming lifestyle has become a trend proofed by the surabayaâs busy culinary business both day and night. From this perspective then, the restaurant can be used as a media to inform to the public about the ecological design.In the city of Surabaya is seldom to find a restaurant that take Ecological Design in their concept. In support of sustainable design, that the restaurant need have to the applicate the ecological design. Apart from being a place to eat, as well as providing information to the community and the effect on the environment, especially natural lighting.